Fusion of the Mycobacterium tuberculosis antigen 85A to an oligomerization domain enhances its immunogenicity in both mice and non-human primates. - Alexandra J Spencer; Fergal Hill; Jared D Honeycutt; Matthew G Cottingham; Migena Bregu; Christine S Rollier; Julie Furze; Simon J Draper; Karen C Søgaard; Sarah C Gilbert; David H Wyllie; Adrian V S Hill (PLoS ONE, 2012)
To prevent important infectious diseases such as tuberculosis, malaria and HIV, vaccines inducing greater T cell responses are required. In this study, we investigated whether fusion of the M. tuberculosis antigen 85A to recently described adjuvant IMX313, a hybrid avian C4bp oligomerization domain, could increase T cell responses in pre-clinical vaccine model species. In mice, the fused antigen 85A showed consistent increases in CD4(+) and CD8(+) T cell responses after DNA and MVA vaccination. In rhesus macaques, higher IFN-γ responses were observed in animals vaccinated with MVA-Ag85A IMX313 after both primary and secondary immunizations. In both animal models, fusion to IMX313 induced a quantitative enhancement in the response without altering its quality: multifunctional cytokines were uniformly increased and differentiation into effector and memory T cell subsets was augmented rather than skewed. An extensive in vivo characterization suggests that IMX313 improves the initiation of immune responses as an increase in antigen 85A specific cells was observed as early as day 3 after vaccination. This report demonstrates that antigen multimerization using IMX313 is a simple and effective cross-species method to improve vaccine immunogenicity with potentially broad applicability.